De novo Sequencing and Transcriptome Analysis Reveal Key Genes Regulating Steroid Metabolism in Leaves, Roots, Adventitious Roots and Calli of Periploca sepium Bunge - Zhang, Jian; Li, Xinglin; Lu, Fuping; Wang, Shanying; An, Yunhe; Su, Xiaoxing; Li, Xiankuan; Ma, Lin; Han, Guangjian (Frontiers in Plant Science, 2017)
Periploca sepium Bunge (P. sepium) is a traditional medicinal plant, whose root bark is the main Chinese herbal medicine. The major bioactive compounds are C21 steroids and periplocin, a kind of cardiac glycoside, which are derived from steroid synthesis pathway. However, the researches on P. sepium genome or transcriptomes and the relative genes have long been untouched until now. In this study, we estimated the nuclear genome size, which was approximately 170 Mb, of P. Sepium using flow cytomet. Then, RNA sequencing of four different tissue samples of P. sepium (leaves, roots, adventitious roots and callus) was performed using sequencing platform Illumina Hiseq 2500. After de novo assembly and quantitative assessment, 90,375 all-transcripts and 71,629 all-unigenes were finally generated. Annotation efforts using a number of public databases resulted in detailed annotation information for transcripts. In addition, differentially expressed genes (DEGs) were identified using digital gene profiling based on reads per kilobase of transcript per million reads mapped (RPKM) values. Compared with leave samples (L), up-regulated genes and down-regulated genes were obtained eventually. To increase our understanding of these DEGs, we performed gene ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis. In this study, we focused on analysis of expression characteristic genes involved in terpene metabolic pathway and steroid biosynthesis pathway, trying to find out molecular mechanism of bioactive steroid synthesis in P. Sepium. By bioinformatics analysis, many genes involved in bioactive steroid biosynthesis were found. These genes included acetyl-CoA acetyltransferase (ACAT), HMG-CoA synthase (HMGS) , HMG-CoA reductase (HMGR), mevalonate kinase (MK), phosphomevalonate kinase (PMK), mevalonate diphosphate decarboxylase (MDD), isopentenylpyrophosphate isomerase (IPPI), farnesyl pyrophosphate synthase (FPS), squalene synthase (SS), squalene epoxidase (SE), cycloartenol synthase (CAS), sterol C-24 methyltransferase (SMT1), sterol-4alpha-methyl oxidase 1 (SMO1), sterol 14alpha-demethylase (CYP51/14-SDM), delta(14)-sterol reductase (FK/14SR), C-8,7 sterol isomerase (HYD1), sterol-4alpha-methyl oxidase 2 (SMO2).delta(7)-sterol-C5(6)-desaturase (STE1/SC5DL), 7-dehydrocholesterol reductase (DWF5/DHCR7), delta (24)-sterol reductase (DWF1/DHCR24), sterol 22-desaturase (CYP710A), progesterone 5beta-reductase (5β-POR), 3-beta-hydroxysteroid dehydrogenase (3β-HSD). This research will be helpful to further understand the mechanism of bioactive steroid biosynthesis in P. sepium, such as C21 steroid and periplocin biosynthesis.